A Causal Linkage Between Corporate Sustainability Performance and Financial Performance of Select IT & ITeS Companies in India - Santhi, P.; Sasirekha, P.; Anija, J. (Indian Journal of Finance, 2024)
Purpose : The present study examined the association between the environmental, social, and governance (ESG) and corporate financial performance (CFP) of select information technology and information technology-enabled services (IT & ITeS) companies in India. Methodology : The independent variables of CFP, namely return on sales, return on asset, return on capital employed, return on equity, and Tobin’s Q and the variables of CSP ESG Score, environmental, social, and governance score individually and control variables firm age and net worth were considered. Causality and influence between CFP and CSP and vice-versa were tested through Grangular causality and panel data regression analysis, respectively, using E-views12. Secondary data were drawn from Integrated Annual Reports of the NSE-rated 27 top disclosure IT & ITeS companies selected on census sampling. Findings : It was demonstrated that there was a bidirectional correlation between ESG and social and governance and unidirectional causality between Tobin’s Q and ESG, ESG to net worth, and ESG to return on sales. IT and ITeS firms support the traditional view that sustainability costs constrain financial performance. Practical Implications : It was suggested the companies consider the elements of sustainability equally to make rational, sustainable investments to augment ESG. Establishing a standard ESG framework would serve as a guide for effective implementation. Originality : The connection and causation between CFP and CSP, as well as vice versa, were examined in the current study. Additional research could look at the national and local business contexts.